PENGUKURAN KINERJA KARYAWAN PADA PT HT MANUFACTURING - Anjani, Restu; Sugianto, Welly (LPPM Universitas Putera Batam, 2023)
This research focuses on measuring the performance of employees at PT HT Manufacturing, a company producing fishing bait and equipment. The study aims to assess employee performance in the Painting department and identify potential areas for improvement. The current performance measurement system is found to be subjective, emphasizing financial targets only. The theoretical framework discusses the concept of performance, performance measurement, human resources management, and the Human Resource Scorecard (HRSC). The HRSC is an important tool for measuring and managing the strategic contributions of human resources to achieve the company's objectives. The research methodology used is a survey, employing questionnaires and interviews to collect data from 24 employees in the Painting department. Data validity and reliability are tested using statistical analyses like correlation and Cronbach's alpha. The findings reveal that most indicators used to measure employee performance are valid and reliable. However, one indicator related to measuring performance between employees and their superiors is found to be invalid. The research concludes that the company's performance measurement needs improvement, and employee training plays a crucial role in enhancing job satisfaction and overall performance.Overall, this study provides valuable insights into the performance measurement process at PT HT Manufacturing and offers recommendations for enhancing employee performance and job satisfaction through effective training programs.